Practices and utility of imaging among urological communities for urolithiasis, observations, and inferences from a targeted survey - ŞAHİN, BAHADIR; ŞENER, TARIK EMRE; TANIDIR, YILÖREN (My University, 2023)
To evaluate the general practice among urologists about the use of various radiological imaging and measurement tools, and to compare the diferent preferences in radiological evaluations between Turkish and European urologists. Our study was designed as a survey study. The survey comprised 22 questions which evaluated the epidemiological information, caseload of participants, general preferences of participants on CT image slice thickness, basic radiologic workup routines prior to surgery, use of special tools and measurements on CT. Data collection was conducted with both an online poll and printed copies. A total of 222 urologists from 23 diferent countries responded to the survey. The most performed endourologic surgery was semi-rigid URS which was performed more than 25 times/year by 90.1% (n=200) of the participants. Although PCNL was performed more commonly by Turkish urologists (39.7%) compared to their European (17.3%) colleagues (p<0.001), it was still the least often performed endourological surgery among all participants (31.5%). The stone size evaluation was the most performed measurement performed by the participants. Although the group of surgeons used size measurement tools, there were diferences between the two groups. Turkish urologists used size measurement before PCNL (85.7%) as opposed to European urologists who used it mostly before URS (91.4%). Non-contrast CT images for urolithiasis are mainly evaluated by urologists themselves and a considerable number of urologists do not use additional measurement tools in evaluating CT images. Although there are similarities in the knowledge of various radiological tools, there are distinct regional diferences. Keywords Urolithiasis · Computed tomography · Evaluation · Survey · Management
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; Üroloji; Urology; Computed tomography; Evaluation; Management; Survey; Urolithiasis